New Developments Integrating Biology And Islam In Learning Process - Zaenab Canu; Puji Dwi Rahayu; Dina Rahmawati (Archipelago, 2020)
This articles to obtain information about the design, steps, and implementation of the teacher in integrated subjects clumps of Biology and Islam. The research method used is qualitative and data collection techniques from literature, journals, scientific articles, and reviews. The results of this research are in the form of design, steps and implementation carried out by the Biology subject teacher in the Islamic-based learning process.Keywords: Integration, Islamic Education, Biology